The relationship between position on an electoral list and chances of winning a seat in a representative body; experiences from the 2015 Sejm election in Poland - Rachwał, Marcin (Przegląd Politologiczny, 2018)
This paper examines the relationship between the candidate’s position on an electoral list and the feasibility of winning a seat in the Sejm (the lower chamber of the Polish parliament). This research hypothesizes that winning a seat strongly depends on the candidate having a top position on the electoral list. This hypothesis is verified vis-à-vis the results of the 2015 election to the Sejm. The study confirmed the initial assumption, since it was found that nearly 82% of the seats were taken by the candidates from the so-called “seat-winning places,” namely the top places on the lists of candidates (the number of these places equals the number of seats taken by a given party in a given constituency).